Aktywność wyborcza mieszkańców w zależności od poziomu rozwoju gmin (na przykładzie wybranych gmin województwa mazowieckiego) - Wojewódzka, Agnieszka (Voter's Activity Depending on Development Level on the Example of Selected Mazowieckie Voivodship Communities, 2008)
The aim of the article is to describe relationships between the election inhabitants' activity and development level of Mazowieckie voivodship communities. On the basis of information from the I Regional Data Bank (prepared by the Central Census Bureau), the author has formed synthetic index | HI the Mazowieckie voivodship communities, which demonstrates the rate of local development. Three criteria were taken under the consideration: the content-related, the formal, and the statistical me, Then, taking into account the indices, the local communities were sorted into a growing order. He objects were divided into two kinds of group, namely there were 25% of the least developed local communities and 25% of the most developed local governments. The factors of local development were presented from a theoretical point of view. The author mentioned that recently economics has concentrated on nonmaterial factors explaining development differences among regions. In the next step, based on the National Electoral Commission data, the turnout in parliamentary and local elections and outcomes in referendum about the EU accession were analyzed. The higher development level is, the higher turnout in EU referendum was and the lower development level is, the smaller turnout in local election was. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 348-355